Streptococcus pyogenes-purpura fulminans as an invasive form of group A streptococcal infection - Sayaka Okuzono (Annals of Clinical Microbiology and Antimicrobials, 2018)
Abstract Background Streptococcus pyogenes is an uncommon pathogen of purpura fulminans, and the pathogenesis of S. pyogenes-purpura fulminans remains unclear because of paucity of cases. We reported a pediatric case of S. pyogenes-purpura fulminans with literature review of the disease. Case presentation A 3-year-old boy showed limping, lethargy and acral gangrene within 24 h. A diagnosis of S. pyogenes-purpura fulminans was made for bacterial isolation from throat and peripheral blood. Intensive therapy led to a survival with amputation of the left distal metatarsal bone, and normal development. The isolated M12 carried no mutation of csrS/R or rgg. Thrombophilia or immunodeficiency was excluded. Discussion Twelve-reported cases (9 pediatric and 3 elderly) of S. pyogenes-purpura fulminans started with shock and coagulopathy. Five patients age < 8 years had no underlying disease and survived. One youngest and two immunocompromised patients died. Conclusion Streptococcus pyogenes-acute infectious purpura fulminans is a distinctive rare form of aggressive GAS infections.